Designing and testing systems of systems: From variability models to test cases passing through desirability assessment. Issue 10 (17th January 2022) - Lonetti, Francesca; de Oliveira Neves, Vânia; Bertolino, Antonia
Abstract: In the early stages of a system of systems (SoS) conception, several constituent systems could be available that provide similar functionalities. An SoS design methodology should provide adequate means to model variability in order to support the opportunistic selection of the most desirable SoS configuration. We propose the VANTESS approach that (i) supports SoS modeling taking into account the variation points implied by the considered constituent systems; (ii) includes a heuristics to weight benefits and costs of potential architectural choices (called as SoS variants) for the selection of the constituent systems; and finally (iii) also helps test planning for the selected SoS variant by deriving a simulation model on which test objectives and scenarios can be devised. We illustrate an application example of VANTESS to the "educational" SoS and discuss its pros and cons within a focus group. Abstract : In this paper, we propose VANTESS, a new variability‐aware approach for designing and testing of SoSs. More specifically, VANTESS supports an SoS engineer in (i) modeling the variation points induced by differing candidate constituent systems; (ii) assessing the benefits and costs of potential SoS variants for the selection of the constituent systems; and (iii) generating a set of functional and robustness test cases.